Faktor yang Berhubungan dengan Pemberian Mp-Asi Dini di Wilayah Kerja Puskesmas Dapurang - Husna Husna; Akmal Novrian Syahruddin; Fitriyah Amiruddin (Pusat Riset dan Inovasi Nasional, 2025)
Providing complementary foods (MP-ASI) that is not appropriate to the timing, either too early or too late, can have negative impacts on children's health, such as malnutrition, decreased immunity, and increased risk of gastrointestinal infections. This study is a quantitative study with an analytical method using a cross-sectional approach. The study population included all mothers with children aged 6–23 months in Dapurang Village, a total of 111 people. Of these, 53 respondents were selected as samples using a purposive sampling technique according to predetermined criteria. The variables studied included maternal knowledge, socio-cultural factors, the role of health workers, and the practice of providing early MP-ASI. Data were collected through questionnaires, then analyzed univariately and bivariately using the chi-square test to see the relationship between variables. The results showed that 62.3% of mothers had good knowledge, 58.4% were still influenced by less supportive socio-cultural factors, and 66% of respondents stated that health workers played an active role. In addition, 64.1% of respondents did not provide early MP-ASI to their children. The results of statistical tests showed a significant relationship between knowledge (ρ = 0.000), socio-cultural factors (ρ = 0.001), and the role of health workers (ρ = 0.002) with the practice of providing early complementary feeding. Therefore, this study concluded that the level of maternal knowledge, socio-cultural support, and the involvement of health workers have a significant influence on the practice of providing early complementary feeding in the Dapurang Community Health Center work area.